Improving Students' Speaking Skills through Learning Media and the Mastery of Different Discourse Markers - Suryadi Suryadi; Asep Muhyidin; Syafrizal Syafrizal; Fajar Erlangga (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to ascertain the differences in improving students' English-speaking skills through using learning media and mastering proficiency in discourse markers. Method: This research uses a quantitative approach and experimental design. The design used the non-equivalent 2 x 3 factorial design. The research sample consisted of 1000 Madrasah Aliyah students in Serang Regency. However, in this study, only 10% of the population 100 was sampled using systematic random sampling techniques. The instruments used to collect data include speaking and discourse marker tests. We analyzed the research data using two-way ANOVA statistics with SPSS 26. Results: The results of this research are grouped into four research findings, namely (1) differences in students' speaking abilities between students who were treated using the learning media Scrabble Word and flashcards, (2) differences in students' speaking abilities with high, medium and low mastery of students' discourse markers, (3) an interaction between learning media and high, medium, and low students' mastery of discourse markers on students' speaking abilities, and (4) differences in mastery of discourse markers based on students' gender, from the average of pre-test and post-test. Novelty: This research is intriguing due to variations from prior studies in emphasis, subjects, outcomes, gender disparities in mastery of discourse markers, and incorporation of research variables. Previous studies concentrated solely on utilizing Scrabble words and flashcards to enhance vocabulary and students' reading abilities. Prior research only examined one research variable, specifically scrabble words, flashcards, and discourse markers.